Differences in the Effects of Chlorhexidine on Optical Density and Colony Count Between Carbapenem-Sensitive and Carbapenem-Resistant Acinetobacter baumannii Strains - Melani, Melani (CV. Publikasi Indonesia, 2025)
Acinetobacter baumannii is a significant nosocomial pathogen with increasing carbapenem resistance. Chlorhexidine is a widely used antiseptic, but its efficacy against carbapenem-resistant strains remains unclear. This study aimed to compare the effects of chlorhexidine on optical density (OD) and colony count between carbapenem-sensitive and carbapenem-resistant A. baumannii strains. An experimental laboratory study was conducted using A. baumannii strains (sensitive and carbapenem-resistant). The strains were exposed to chlorhexidine (0.25% and 0.5%) for 20–120 seconds. OD was measured spectrophotometrically, and colony counts (CFU/mL) were determined after incubation. Data were analyzed using the Kruskal-Wallis test. Carbapenem-resistant strains showed higher tolerance to chlorhexidine, with slower reductions in OD and colony counts compared to sensitive strains. Significant differences were observed in colony counts after exposure to 0.5% chlorhexidine for ≥60 seconds (p < 0.05). OD values were less sensitive to exposure duration but varied significantly with concentration (p < 0.05). Chlorhexidine remains effective against carbapenem-resistant A. baumannii, but higher concentrations (0.5%) and longer exposure times (≥60 seconds) are required for optimal eradication. These findings support tailored antiseptic protocols in clinical settings with high resistance prevalence.